The Influence of Brand Ambassador, Brand Awareness, and Price on Brand Image and Purchasing Decision in Halal Skincare Product (Study on MS Glow Skincare Products in Surabaya) - Indina Ni’ma Sam Ardian; Rachma Rizqina Mardhotillah (Journal of Halal Research, Policy, and Industry, 2023)
The influence of technology in everyday life can influence a person's buying decision. Companies must be up to date in seeing existing developments and changes. This study aims to determine whether there is an influence of Brand ambassador, Brand awareness and Price on Brand image and Purchasing decision. The population in this study is consumers who have purchased Ms.glow products domiciled in Surabaya. The sample of the study was 227 respondents obtained in the purposive sampling research method. The data analysis method in this study uses path analysis with smartPLS software. The results of the study showed a significant influence between Brand ambassadors on Brand image and not significant on Purchase decisions. There is a significant influence between Brand awareness and Price on Brand Image and Purchasing decisions. And there is a significant influence of Brand image on Purchasing decisions.